2018
DOI: 10.1016/j.adolescence.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of self‐efficacy and educational aspirations for academic achievement in resource‐limited countries: Evidence from Ghana

Abstract: Introduction: Research on the influence of academic self-efficacy and educational aspirations on academic performance is underdeveloped in resource-limited countries. This study replicates and expands on earlier research that investigated a complex network of relationships between academic self-efficacy, educational aspirations, and academic performance. Methods: Data from 4282 adolescents in Ghana and path analysis were used to test the causal pathways, and path invariance analysis was used to assess the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
3
18
0
2
Order By: Relevance
“…Previous studies had indicated the association between academic achievement with self-efficacy and SC. [ 16 17 28 ] It is emphasis high level of self-efficacy can decrease the educational burnout and cause ability in the adolescents’ education. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had indicated the association between academic achievement with self-efficacy and SC. [ 16 17 28 ] It is emphasis high level of self-efficacy can decrease the educational burnout and cause ability in the adolescents’ education. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the mediator role of self-efficacy and SC had been shown in the path diagram of different constructs such as academic stress and life satisfaction, motivation, emotion, and academic achievement. [ 14 15 16 17 18 ] Subsequently, fostering these constructs will promote psychological well-being and influence students’ educational outcomes. [ 19 ] School-related factors in adolescence period, health behaviors, and family situation of adolescents have an important role on their health.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond executive functions, children's academic achievement is influenced by a multitude of factors including educational opportunities, socioeconomic status (SES), health and nutritional status, as well as the family environment. Again, most of the current empirical evidence is based on children from high-income countries [10], although similar associations have been described in low-and middle-income countries (LMICs) [11,12]. However, children living in socioeconomically deprived environments are facing additional challenges [13].…”
Section: Introductionmentioning
confidence: 95%
“…The atmosphere that involves a generative ability and organized the innumerable purposes is combined developments of action into behaviors, social, and cognitive are called Efficacy (Peleg & Idan-Biton, 2018). Individual"s beliefs in their particular skills to achieve a certain task with preferred outcomes have been defined as self-efficacy (Ansonga, Eisensmith, Okumu, & Chowa, 2019). Bandura (1994) suggested that self-efficacy covered many situations, self-efficacy is different in different people some individuals have a solid sense of self-efficacy and others have not.…”
Section: Introductionmentioning
confidence: 99%